2021
DOI: 10.1002/mds.28885
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SPAST Mutation Results in Spastin Accumulation and Defects in Microtubule Dynamics

Abstract: Background Haploinsufficiency is widely accepted as the pathogenic mechanism of spastic paraplegia type 4 (SPG4). However, there are some cases that cannot be explained by reduced function of the spastin protein encoded by SPAST . Objectives To identify the causative gene of autosomal dominant hereditary spastic paraplegia in three large Chinese families and explore the pathological mechanism of a spastin variant. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To date, different mechanistic hypotheses for the etiology of truncating variants in SPAST-HSP have been proposed. We have summarized the pathogenic truncating variants that have had transcription or protein expression analysis performed in previous studies (Supplementary Table 4) (16, [18][19][20][21][22][23][24][25][26]. Haploinsufficiency has been the explanation for truncating SPAST mutations in the majority of the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, different mechanistic hypotheses for the etiology of truncating variants in SPAST-HSP have been proposed. We have summarized the pathogenic truncating variants that have had transcription or protein expression analysis performed in previous studies (Supplementary Table 4) (16, [18][19][20][21][22][23][24][25][26]. Haploinsufficiency has been the explanation for truncating SPAST mutations in the majority of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, some truncating variants (c.550dupT, c.734C > G, and c.985dupA) escape degradation and are stable. Their truncated mutant proteins could accumulate to a higher level than their wild-type counterparts, indicating possible gain-of-function mechanisms ( 18 , 20 ). The authors concluded that premature stop codons caused by SPAST mutations do not always result in haploinsufficiency ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microtubules encourage the growth of axons in central nervous system neurons and help maintain the neurons’ morphology, transport, and motility, along with maintaining the complexity of neutrine arrangement and degradation. Spastin protein encoded by the SPAST gene is necessary for maintaining microtubule dynamics, and its mutation is linked with SPG4 [ 37 ]. Spastin serves microtubules in more stable regions by targeting tubulin post-translation [ 38 , 39 ].…”
Section: Cells Involved In Hsps Pathologymentioning
confidence: 99%